Upaya Hukum dalam Pencegahan Klaim Tiongkok terhadap Laut Natuna Utara - Budiono, Indro; Anggriawan, Ferry; Kusumandaru, Pena (Bhirawa Law Journal, 2024)
The United Nations Convention on the Law of the Sea (UNCLOS) in 1982 is an international legal The United Nations Convention on the Law of the Sea (UNCLOS) in 1982 is an international legal instrument that plays a key role in regulating the rights and obligations of countries related to the global use of the sea. Territorial conflicts in the North Natuna Sea, especially China's claims that are not by UNCLOS, are a serious challenge for Indonesia in upholding its maritime sovereignty. The 2016 South China Sea Arbitration Award, which rejected China's "Nine-Dash Line" claim, provided a strong legal basis for Indonesia to fight the unilateral claim. This study uses normative juridical methods with historical approaches and case studies, analyzing how the 1982 UNCLOS and the 2016 Arbitral Award are applied in the context of the North Natuna Sea. The results show that the 1982 UNCLOS, in particular Article 73, provides a legal basis for Indonesia to take decisive action in defending its EEZ, while the 2016 Arbitral Award strengthens the legitimacy of Indonesia's rejection of China's claimms. Thus, this research contributes to a deeper understanding of international legal strategies that Indonesia can adopt in facing maritime challenges in the North Natuna Sea.